2019
DOI: 10.1038/s41467-019-11964-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ferroelectricity-driven Berry curvature enabling charge- and spin-controllable photocurrent in tin telluride monolayers

Abstract: In symmetry-broken crystalline solids, pole structures of Berry curvature (BC) can emerge, and they have been utilized as a versatile tool for controlling transport properties. For example, the monopole component of the BC is induced by the time-reversal symmetry breaking, and the BC dipole arises from a lack of inversion symmetry, leading to the anomalous Hall and nonlinear Hall effects, respectively. Based on first-principles calculations, we show that the ferroelectricity in a tin telluride monolayer produc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 46 publications
4
75
2
Order By: Relevance
“…In addition, previously unknown phonon-phonon and electron-phonon scattering mechanisms could arise from topological phonons, which may provide new insights into the enhanced superconductivity of SrTiO 3 ( 26 , 59 ). The emergence of Weyl phonons may be accompanied by other unique physical properties such as a pseudogauge field with a one-way propagating bulk mode ( 60 62 ), topological negative refraction ( 18 ), and nonlinear acoustic/optical responses ( 63 , 64 ), which can offer new routes for designing novel technologies like light-controlled neuromorphic computing in phononic systems ( 65 , 66 ). Our work shows that oxide perovskites provide a promising platform to explore all of these phenomena and applications.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previously unknown phonon-phonon and electron-phonon scattering mechanisms could arise from topological phonons, which may provide new insights into the enhanced superconductivity of SrTiO 3 ( 26 , 59 ). The emergence of Weyl phonons may be accompanied by other unique physical properties such as a pseudogauge field with a one-way propagating bulk mode ( 60 62 ), topological negative refraction ( 18 ), and nonlinear acoustic/optical responses ( 63 , 64 ), which can offer new routes for designing novel technologies like light-controlled neuromorphic computing in phononic systems ( 65 , 66 ). Our work shows that oxide perovskites provide a promising platform to explore all of these phenomena and applications.…”
Section: Resultsmentioning
confidence: 99%
“…is Berry curvature dipole (Λ) along a-direction,ẑ is the normal unit vector perpendicular to the plane made up of D and E, and f occ , τ are occupation of Bloch state and constant 10 . As discussed previously, the Berry curvature dipole directly scales with the polarization that measures the amount of inversion-symmetry breaking of the lattice 10,16 . Here we focus on the fact that the lattice distortion along the A u mode enhances the net in-plane polarization and leads to an increase in the Berry curvature dipole.…”
Section: Charge Oscillation and Photovoltaic Response Functionsmentioning
confidence: 82%
“…1d. Previous studies have suggested that this asymmetric Berry curvature can be attributed to the orbital Rashba effect 16 . Upon hole doping, this asymmetry in the Berry curvature grants sizable Berry curvature dipole (Λ y ) in the in the y-direction which can be manifested helicity-dependent second-order electro-optical responses 10,11 .…”
Section: Atomic Geometry and Electronic Structure Of Monolayer Sntementioning
confidence: 90%
See 2 more Smart Citations